PENERAPAN DISTRIBUSI PROGRAM BANTUAN PADA WARGA MISKIN BARU DITINJAU DARI HUKUM EKONOMI SYARIAH (Program Studi Muamalah Fakultas Syariah dan Hukum, 2022)
This study aims to determine how the application of aid distribution to the new poor and Sharia Economic Law Review on the application of the distribution. Food assistance is a program from the government to reduce the burden on the community in dealing with the current COVID-19 pandemic. The government has issued various policies to deal with the COVID-19 pandemic. This research includes field research (field research). This research is seen from its nature, including descriptive qualitative research, while the data collection methods are carried out by means of observation, interviews, and documentation. Interviews were conducted with residents who received assistance and sub-district employees to obtain data for conducting research. And the data analysis used in this research is inductive thinking.